Analisis Fenomena Tawuran Remaja dalam Perspektif Perilaku Menyimpang : Studi Kasus di Daerah Manggarai, Jakarta Selatan - Ciek Julyati Hisyam; Mayang Puti Seruni; Diva Kayla Nazwa Anas; Faridah Faridah; Nindia Monita Br Ginting; Siti Umi Khoiriah; Syafa Marwah Augea; Vinsensia Carolin Purba (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2025)
The phenomenon of teenage brawls in the Manggarai area, South Jakarta, reflects deviant actions influenced by social and cultural conditions in society. These disputes are triggered by a number of factors, such as competition between groups, lack of parental supervision, limited access to positive activities, and provocations carried out through social media platforms. In this case, Robert K. Merton's anomie theory is applied to analyze how the mismatch between social goals and legitimate means drives teenagers to take the path of violence in order to gain social recognition and group solidarity. This study applies a qualitative descriptive approach using in-depth interview techniques and participant observation of community leaders in RW 04, RW 05, and RW 12. The research findings show that brawls in Manggarai are more than just juvenile delinquent behavior, but are a form of response to social pressure and lack of opportunities for self-realization. The social consequences of these brawls include psychological trauma, social stigma, and disruption to the stability of the surrounding environment. However, the local community has tried to prevent this by implementing a religion-based approach, skills training, and strengthening coordination between regions. This study emphasizes that structural interventions and community-based approaches are key to addressing the root causes of brawls in a comprehensive and sustainable manner.